Buckling strength of steel tube for lifting telescopic wind steel tower. (March 2021) - Campione, G.; Cannella, F.; Zizzo, M.; Pauletta, M.
Highlights: Telescopic tower for wind energy production with low environmental impact. Tower, raised and lowered by automation. Lifting system consisted of a buoyant hull fitted with a number of movable legs. Lateral restraints to increase the buckling load during the elevation operation. Abstract: A telescopic pole for wind energy production with low environmental impact and its lifting system for a 60–250 kW turbine and a height of 30 m have been designed and manufactured. The tower, was raised and lowered by automation or by remote control, that allows one to differentiate the presence of the generator within the landscape over time. The jacking systems acting on the legs had a combination of holes (on the legs) and pegs actuated by hydraulic pistons. The aim of the paper was the experimental and the analytical verification of the stability condition of the steel piston as a lifting system of the prototype. An experimental investigation was carried out on small-scale specimens to examine the influence of lateral restraints constituted by external steel tubes and transverse devices to increase the buckling load and to ensure a stability condition during the elevation operation of the telescopic steel pole. Finally, the experimental results were numerically validated. The original contribution of the paper to research was the design of lifting system of telescopic wind tower though a steel piston with transverse stiffeners.